Phenotypic characterisation of Pasteurella multocida obtained from poultry in Iran - A.R., Jabari; Abdul Aziz, Saharee; F., Esmalaily (Veterinary Association Malaysia, 2003)
Phenotypic patterns of twenty-five isolates of P. multocida strains isolated from northern provinces of Iran were determined by using different carbohydrates from hexoses, pentoses, disaccharides and polyhydric alcohols. The strains showed a high homogeneity. All strains were able to ferment sorbitol, mannitol, galactose, dextrose, fructose, glucose, mannose and sucrose. However none of them could produce acid from dulcitol, inositol, arabinose, salicine, raffinose and inoline. According to this pattern all of isolates belonged to subspecies multocida. The in-vitro sensitivity of isolates against 13 chemotherapeutic agents was determined by the paper disc method. Among the antibiotics tested, chloramphenicol, combination of sulfamethoxazine and trimethoprim and nitrofurantoin were found to be the most effective (100%) followed by tetracycline (96%), penicillin (88%), and gentamicin (76%). Strains showed 100% resistance to lincomycin and bacitracin followed by 84% and 68% resistance to furazolidone and colistin respectively. All P. multocida isolates identified as to capsular type A.